Homicides in the city of Manaus: An analysis of lethal violence in the largest capital of the Brazilian Legal Amazon (Research, Society and Development, 2025)
The article “Homicides in the City of Manaus: An Analysis of Lethal Violence in the Largest Capital of the Brazilian Legal Amazon” investigates the dynamics of homicides in Manaus, contextualizing lethal violence from socioeconomic, territorial, and institutional perspectives. Based on the research, we highlight that homicide is the ultimate expression of violence, often linked to social inequalities and the absence of effective public policies. Brazil leads in absolute homicide numbers, with rates significantly higher than the global average, especially among Black youth and residents of peripheral areas. Therefore, the aim of this article is to analyze homicide rates in the city of Manaus/AM. The research adopts an exploratory quantitative approach, using data from the Integrated Public Security System (SISP) and a bibliographic review. The results indicate that between 2023 and 2024, the number of homicides decreased from 1,408 to 1,084, with reductions also observed in cases of robbery followed by death (latrocínio) and bodily injury resulting in death. On the other hand, femicides increased, highlighting the need for policies to protect women. No cases of torture resulting in death were recorded in 2024. The northern and eastern zones of the city have the highest homicide rates, reflecting socioeconomic and structural disparities. The integration of the Integrated Police Districts (DIPs) with the Community Interactive Company (CICOM) has contributed to faster and more effective responses.